2019
DOI: 10.1213/ane.0000000000003956
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of the Pediatric Patient on Medicinal Marijuana: What Anesthesiologists Should Know

Abstract: In 2018, 29 states allow the use of medicinal marijuana. In these states, minors, with parental permission, are granted access. Use has increased in some states, although there remains a paucity of clear evidence regarding usefulness and dosing. There are 2 Food and Drug Administration–approved synthetic derivatives. One purified compound was just approved by the Food and Drug Administration, and another is undergoing Food and Drug Administration review. This article will review the literature regarding the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Prescribed cannabinoids: Although uncommonly prescribed, Sativex and Epidyolex are licensed for use in the UK as of November 2019 (NICE 2019). However, for paediatric patients in the US on FDA-approved synthetic cannabinoids, prescribed doses are advised to be continued on the day of surgery (Flannery et al 2019). Care should be taken, however, as there is a concern with the additive effects of sedatives, especially benzodiazepines (Flannery et al 2019).…”
Section: Discussion: Anaesthetic and Perioperative Implications Of Ma...mentioning
confidence: 99%
“…Prescribed cannabinoids: Although uncommonly prescribed, Sativex and Epidyolex are licensed for use in the UK as of November 2019 (NICE 2019). However, for paediatric patients in the US on FDA-approved synthetic cannabinoids, prescribed doses are advised to be continued on the day of surgery (Flannery et al 2019). Care should be taken, however, as there is a concern with the additive effects of sedatives, especially benzodiazepines (Flannery et al 2019).…”
Section: Discussion: Anaesthetic and Perioperative Implications Of Ma...mentioning
confidence: 99%
“…45 Recent cannabis use is associated with increased risk of perioperative acute myocardial infarction (MI), while chronic use may be associated with increased postoperative pain and postoperative nausea and vomiting (PONV). 40,46 To date, there are no published studies that investigated cardiac issues specifically among adolescents who vaped. 47 Studies in adolescents who use e-cigarettes have found a higher incidence of asthma, wheezing, or chronic bronchitis symptoms including chronic cough, phlegm, or bronchitis.…”
Section: The Youth Vaping Epidemic and Rise In Cannabis Usementioning
confidence: 99%
“…They quote a study that found that treatment with cannabis was ineffective in reducing pain and postoperative opioid consumption, while the administration of higher doses of cannabis decreased frequency of breakthrough pain while increasing sedation. However, they do not mention that there are recent studies that have reported analgesic and opioid-sparing effects of cannabis in acute pain setting with no increased adverse events …”
mentioning
confidence: 94%
“…The onset of withdrawal symptoms generally occurs within 1 to 2 days, and the symptoms typically peak within 1 week and dissipate within about 2 to 4 weeks. Therefore, recent publications mention practice of continuing cannabis until the day of surgery and providing cannabis to chronic cannabis consumers postoperatively …”
mentioning
confidence: 99%